INNOVATIVE INTERACTIVE LEARNING STRATEGIES IN TEACHING QUR’AN AND HADITH AT THE MADRASAH TSANAWIYAH LEVEL - Winda Astuti; Nurlaili (Edukasi: Jurnal Pendidikan, 2025)
This study explores a novel integration of technology-based interactive learning strategies in Al-Qur’an Hadith instruction at MTs Harsallakum Bengkulu. Unlike traditional approaches that rely heavily on lecturing and memorization, this model emphasizes active student engagement through digital tools such as interactive videos, quizzes, and group discussions. Using a qualitative Classroom Action Research (CAR) method over two cycles planning, implementation, observation, and reflection data were collected via observations, interviews, documentation, and student assessments. The findings reveal significant progress: student participation increased from 12 to 24, average scores rose from 65 to 82, and notable improvements were observed in enthusiasm, religious behavior, and teacher creativity. The novelty lies in contextualizing Islamic learning with modern technology, making religious education more relevant, participatory, and impactful. This approach not only enhances academic performance but also strengthens Islamic character, demonstrating its effectiveness in aligning traditional religious content with contemporary educational practices.